On the recent designation of a neotype for the taxon Calotes versicolor (Daudin, 1802) (Reptilia: Agamidae) - Chaitanya, R.; Giri, Varad B.; Deepak, V. (Zootaxa, 2017)
Calotes versicolor (Daudin, 1802) is a widespread species of agamid lizard found commonly in the Indian subcontinent and the Indo-Chinese region with a complicated taxonomic history (Uetz & Hosek, 2016). The type locality of this species has been debatable (Smith, 1935, Amarasinghe et al. 2009) and the recent designation of a neotype from Pondicherry by Gowande et al. (2016) though much warranted, introduces additional complications that impede a thorough taxonomic resolution of this species complex.